An Experimental Study to Assess the Scope of Homoeopathy in Obesity of Children, with its Homoeopathic Management (Advancements in Homeopathic Research, 2024)
BACKGROUND-Obesity is one of the greatest  public health challenges worldwide. Now a days  it is more common in children also. It is not only  a medical but also a philosophical, ecological,  economic, sociocultural, and psychological  problem as well as a severe consequence of our  modern value definition to 'receive more and  more'. Therefore, physicians are not able to treat  obesity broadly and should not be used any tools  to achieve certain weight goals. Homoeopathic  literatures speak volumes of treatment of such  cases.
Keywords: Body mass index; Obesity; Homoeopathy